Acessibilidade espacial no ambiente construído : um estudo nas escolas de ensino fundamental do município de Canoas, RS - Dipp, Guilherme Händel (2013)
The Brazilian laws guarantee the right to school inclusion to people with disabilities at regular schools. Each year the enrollment of such students at state schools has been increasing all around the country. However, full inclusion will only be effective if the schools become accessible. It is through the disruption of the physical barriers that architecture may provide its contribution. This means providing not only the access to the building, but also the permanence and the participation of the students with disabilities and limited mobility in the school s various environments and activities. Thus, this work is part of an exploratory study on the conditions of spatial accessibility in elementary schools, aiming at improving the adequacy of the municipal schools regarding the needs of such students. Taking as case study twelve municipal schools from the city of Canoas, this research first analyses the surroundings of these buildings and then the building itself, identifying the main difficulties that the environment that was built presents to the students with disabilities and limited mobility. Through a technical analysis it was possible to verify, initially, that none of the schools that were studied meets all the criteria of spatial accessibility discussed, showing that the education network presents a framework which requires more attention from the public authorities. Later on, through a behavioral analysis with the users of the spaces it was possible to verify the students high level of satisfaction with the quality of the spatial accessibility of the school building, even though many recommendations regarding the improvement of the spaces that were studied have been proposed, even those within the area of public policies and those regarding the performance of the agencies involved. We expect to provide, with this research, technical-constructive subsidies to the planning and to the spatial accessibility projects of this city s schools, as well as to contribute in the divulgation of studies in this area of knowledge.